Resistance of cotton genotypes to Sclerotinia sclerotiorum by the straw and oxalic acid tests - Aguiar, Leandro Henrique Mundim; Sousa, Larissa Barbosa de; Coelho, Lisias; Lemes, Ernane Miranda; Castro, Leonardo Humberto Silva e; Cardoso, Daniel Bonifácio Oliveira (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the efficiency of the straw and oxalic acid tests to identify resistance levels of white and colored cotton (Gossypium hirsutum) genotypes to white mold (Sclerotinia sclerotiorum). Ten genotypes were evaluated: five with colored fiber, four with white fiber, and a white-fiber susceptible genotype. The genotypes MAB-1 with white fiber and MAC-2 with colored fiber were the most resistant to white mold, according to the immersion in oxalic acid and straw tests, respectively. These genotypes can be recommended as resistance sources for breeding programs. Both assessed tests are complementary to each other; however, the straw test is more efficient in evaluating the resistance of cotton genotypes to white mold.